Structural‐functional unit ordering for high‐performance electron‐correlated materials. Issue 1 (2nd January 2023) - Peng, Guyang; Hu, Lei; Qu, Wanbo; Zhang, Chenglong; Li, Shurong; Liu, Ziyu; Liu, Juncheng; Guo, Shengwu; Xiao, Yu; Gao, Zhibing; Zhang, Zhen; Zhang, Yang; et al.
Abstract: Electron‐correlated materials have been drawing ever‐increasing attention due to their fascinating physical behaviors and extensive application scenarios. In this review, a new method for material research and design (R&D), named structural‐functional unit ordering (SFU ordering), which is presented, overcomes the shortcomings—for example, the limitation of finite chemical elements and long R&D circle‐of conventional strategy and thus provides guidance for the design of these high‐performance functional materials on demand. Meanwhile, with the development of material characterization technologies, SFUs of different scales and types can be directly observed, which, moreover, regulate the corresponding orderings. The review, starts with an introduction of the profile for SFU ordering and the synergistic effect between SFUs. Then, studies on several new high‐performance electronic‐correlated materials, for example, a ferromagnetic semiconductor with local spin, ferromagnetic metals with spin topologies, ferroelectric thin films with polar topologies, piezoelectric thin films with nanopillars enclosed by charged boundaries, thermoelectric materials with local ferromagnetic nanoparticles and topotactic phase transformation with conducting nanofilaments are stated in detail one by one. The vital aspect is the breaking of local symmetry, the construction, the structure, of SFUs and their orderings existing or theoretically existing, together with the enhanced/new performance. All in all, the main comments of the review tend to the remaining challenges, promising design approaches for the SFUs, and their orderings for high‐performance functional materials. Abstract : From the perspective of "SFU‐Ordering‐Performance", where SFU is a structural‐functional unit, we investigated and reviewed six different electron‐correlated material systems. It starts from the construction process, the mechanism of SFU ordering in these examples, and the enhanced/new performance and application prospect of the corresponding materials. Then, a brief overview and prospects are provided about how the SFU ordering strategy may evolve in the future.